Rekayasa Pemodelan Biologi Pohon Pepaya (Carica Papaya L.) Pada Fase Vegetatif Sampai Awal Fase Generatif - Riski, Riski Miftahul Ulum; Furoidah, Nanik (JURNAL AGROPLANT, 2022)
Indonesia has various types of fruit throughout the archipelago, one of which is papaya (Carica papaya L.). It can be said that almost all Indonesian people know and love this fruit. Papaya is a commodity that has many functions and benefits, besides fresh fruit, papaya has high economic value, and can meet nutritional needs. Traditionally, the papaya plant is easily cultivated by farmers, and can be used as a strategic commodity to meet most of the food needs of the Indonesian people. Papaya productivity can be increased by pruning the trunk, it can also be done by inserting 2-3 feet of lower stems from several papaya plants in one parent tree connection (merging). One of the biological modeling is the merging of two plants in one plant which is known as grafting. Biological modeling is an engineering technique term to increase plant productivity, in this case papaya can be done one of them by grafting. To determine the effect of the growth of several biological models of papaya in the vegetative phase to the beginning of the generative phase. To determine the effect of the growth of several biological models of papaya in the vegetative phase to the beginning of the generative phase. This research was conducted using a factorial pattern with a Randomized Block Design (RAK), consisting of two factors and three replications. Factor I is the top connection of papaya calina (A) A1: one-branched scion connection, A2: two-pronged scion connection, A3: three-pronged scion connection, Factor II is the bottom connection for rooting (B), B1: stem connection one-legged bottom, B2: two-legged rootstock connection   Keywords: Biological modeling, grafting, merging.